Design of Longwall Coal Pillar for the Prevention of Water Inrush from the Seam Floor with Through Fault. (22nd July 2021) - Li, Ang; Ji, Bing nan; Ma, Qiang; Liu, Chaoyang; Wang, Feng; Ma, Li; Mu, Pengfei; Mou, Lin; Yang, Yuxuan; Ding, Xuesong
Abstract : Setting up a waterproof coal pillar is an important measure to prevent water inrush from the Weibei mining through fault floor. Based on the plastic slip line field theory, a mechanical model of floor water inrush induced by confined water in the through fault zone was established. The mechanical expressions of confined water pressure and the width of the waterproof coal pillar under the state of limit equilibrium were derived. Combining the laws of floor deformation, failure and fault activation under two kinds of coal pillar width, the safety width of the waterproof coal pillar was determined. Furthermore, the safety threshold is better than the empirical value mentioned in the "coal mine safety regulations." Following this, grouting transformation was carried out on the K2 sand layer of the cut roadway floor. This provided a theoretical basis and engineering practice for water disaster prevention and the control of the structural floor under similar conditions in the Weibei mining area for future benefit.